Digital Literacy Boost Students' English Achievement - muhammad saeful haddy; Syauqy Ibnu Shodiq, Muhammad Zacky; kusniyanto, Royan (International Journal of Innovation Research in Education, Technology and Management, 2025)
Digital literacy has become an essential competency for students in the 21st century, particularly in supporting English language learning. This study aims to (1) describe the digital literacy profile of eighth-grade students at MTs Ishlaahul Ummah, (2) examine their English achievement, and (3) analyze the correlation between digital literacy and English achievement. A quantitative correlational method was employed with a sample of 98 students selected through random sampling. Data were collected using questionnaires and school documentation and analyzed with descriptive statistics and simple linear regression. The findings indicate that students’ digital literacy levels vary, with the majority in the low category, while their English achievement mostly falls within the moderate range. Regression analysis revealed a positive and significant relationship between digital literacy and English achievement, with digital literacy contributing 9% to students’ performance. These results highlight the importance of strengthening digital literacy skills as a strategy to enhance English learning outcomes. The study provides practical implications for teachers, schools, and policymakers to integrate digital literacy into learning practices to better prepare students for academic and global challenges.